EFFECT OF ORGANIC FERTILIZER EXTRACT ( X – HUMATE 85 ) AND APPLICATION METHOD ON GROWTH AND YIELD OF APRICOT TREES LABEEB-1 CV. - & et al., Kadhim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This rsearch was conducted on apricot trees cv. Labeeb at the college of Agriculture – University of Baghdad/ Abu Gharib during the growing seasons 2013 and 2014, to investigate the effect of organic fertilizer extract and the method of application on growth and yield parameters, the extract was applied in the biggning of spring by two ways the first foliar application with three concentrations 1, 2 and 3 g.L-1 and second ground application 2, 4 and 6 g.L-1. The experiment were designed using Randomized Complete Block Design (R.C.B.D) and Genstat program for statistical analysis. Results of the first season showed that the foliar spraying with high concentration gave highest values for branches length, leaf area and fruit set percentage (12.39 cm), (20.86 cm2) and (10.62%)respectively, while the ground application superior in the high level by gaving leaves dry weight was 45.64%, but the results completely differed in the second season. The foliar spraying with higher concentration caused high content of chlorophyll in the leaves during both seasons (28.68) and (31.22) SPAD unit respectively, while applying of extract in the soil with high level showed highest yield quantity (16.957 and 18.207 kg.tree-1) respectively for both seasons. Ground application was the best method for fertilization with X-Humate85 extract.